A Review of the Impact of Green Tea (Camellia sinensis L.) on Oral Health - Alagarsamy, Karthikeyan; Chaiyasut, Chaiyavat; Kesika, Periyanaina; Sivamaruthi, Bhagavathi Sundaram (Current Pharmaceutical Design, 2025)
In recent years, green tea (<span class=
Keywords: periodontal disease